Management of preterm premature rupture of membrane in a high-risk pregnancy - Bhardwaj, Avni; Simpatwar, Sonam; Afreen, Munazza; Kumari, Beena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Preterm premature rupture of membranes (PPROM) usually has a multi factorial aetiology that is often unknown, although the most frequently reported cause is infection, others could be cervical insufficiency, over distention of uterine cavity, previous history of preterm labor, systemic inflammatory disease etc. This case report documented a rare incidence of preterm premature rupture of membranes, in a 35-year-old female with past history of 8 spontaneous abortions and 1 ectopic pregnancy. Patient had an IVF conception, amenorrheic for 7 months and 2 weeks, and came with a complaint of white discharge per vaginum. On per speculum examination, cervical os was found dilated. The patient was managed conservatively with protein and progesterone support along with prophylactic tocolytics and antibiotics, till early signs of chorioamnionitis were noticed. The decision of induction of labour and eventually preterm premature rupture of membranes lead to emergency cesarean section. Challenges faced in managing this high risk pregnancy are discussed, emphasizing the need of close monitoring and tailoring management in similar circumstances.